Capacity Development in Agricultural Education and training in Cambodia: A SWOT Analysis - Thomas Gill; Vincent Ricciardi; Ricky Bates; Dana James (Journal of International Agricultural and Extension Education, 2017)
This paper examines the current state of the agricultural education and training (AET) system in Cambodia and provides recommendations for Cambodian institutions and policymakers for enhancing the AET system. We conducted two assessment trips in June 2013 and January 2014 to analyze the state of the Cambodian AET system. Data were collected in 53 interviews and five focus groups using a modified-SWOT analysis framework. Stakeholder-identified strengths of the Cambodian AET system include the current political and economic stability of Cambodia, the young labor force, the increased educational enrollments, new agricultural education schools and curricula, good AET leadership, and the wide applicability of AET skillsets. Weaknesses of the Cambodian AET system include weak infrastructure, pedagogical stagnation, skills supply, the disconnect between the supply and workforce demand, and weak institutional administrative expertise. Meanwhile, threats to strengthening the Cambodian AET system include limited public investment, the gap between agriculture and education, low status of agriculture, and poor access to higher education. Recommendations for institutional capacity development in the Cambodian AET system include enhancing skill development and furthering links with NGOs and the private sector, while policy recommendations include welcoming prudent regional integration and enhancing investment across the whole AET system. Comparing our findings to other recent AET system studies indicates that Cambodia is facing similar challenges yet has its own unique path to forge when developing a cohesive AET system capacity-development strategy.
Keywords: Capacity development; Cambodia; Agricultural education and training; AET system; Human and institutional capacity